A Pediatric Patient with Refractory Seizures and a Mesial Temporal Lobe Lesion - McGinley, Marisa; Chen, Haiyan; Anderson, Douglas; Asconape, Jorge; Biller, José (Frontiers in Neurology, 2015)
A 12 year old adolescent presented with refractory seizures and was found to have a mesial temporal lobe lesion. The patient underwent biopsy and was diagnosed with an arteriorvenous malformation. Supratentorial lesions in the pediatric population can have a large variety of underlying etiologies and it can challenging to differentiate on neuroimaging. In this report we discuss the key features on MRI of several neoplastic, vascular, and infectious processes that can aide in the diagnosis.